Role of Mast Cells and Type 2 Innate Lymphoid (ILC2) Cells in Lung Transplantation - Esmaeil Mortaz; Saeede Amani; Sharon Mumby; Ian M. Adcock; Mehrnaz Movassaghi; Jelle Folkerts; Johan Garssen; Gert Folkerts (Journal of Immunology Research)
The multifunctional role of mast cells (MCs) in the immune system is complex and has not fully been explored. MCs reside in tissues and mucous membranes such as the lung, digestive tract, and skin which are strategically located at interfaces with the external environment. These cells, therefore, will encounter external stimuli and pathogens. MCs modulate both the innate and the adaptive immune response in inflammatory disorders including transplantation. MCs can have pro- and anti-inflammatory functions, thereby regulating the outcome of lung transplantation through secretion of mediators that allow interaction with other cell types, particularly innate lymphoid cells (ILC2). ILC2 cells are a unique population of hematopoietic cells that coordinate the innate immune response against a variety of threats including infection, tissue damage, and homeostatic disruption. In addition, MCs can modulate alloreactive T cell responses or assist in T regulatory (Treg) cell activity. This paper outlines the current understanding of the role of MCs in lung transplantation, with a specific focus on their interaction with ILC2 cells within the engrafted organ.